Spectral redistribution of waveguided emission in BEH-PPV films - Cury, L. A.; Miranda, P. B. (Taylor & Francis Ltd, 2002)
We report on spectral redistribution of the photoluminescence (PL) emission from the edge of thin-film planar waveguides of the conjugated polymer BEH-PPV [Poly(2,5-bis(2'-ethyl-hexyl)-1,4-phenylenevinylene] induced by self-absorption in the polymer film. The PL spectra present drastic changes and displace to longer wavelengths with increasing self-absorption. We observe an enhancement of the absolute PL intensity at longer wavelengths, which was interpreted as due to re-emission of self-absorbed photons. The significant efficiency for the PL re-emission suggests the use of self-absorption as a mechanism for tuning the emission into the near infrared.
Keywords: BEH-PPV; photoluminescence; self-absorption; thin-film waveguides; spectral redistribution; conjugated polymers